BEYOND ADVERTISING: MIXED METHOD ANALYSIS OF WEB SERIES AS A NEW WAY TO BUILD BRAND IDENTITY - Ratih Pandu Mustikasari; Ade Kusuma; Sekar Arum Nuswantari (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2026)
Web series, as an alternative to introducing the value of a brand, are currently in great demand. The data shows that web series are currently not only produced as digital content but also for commercial purposes. The intended commercial interests are related to brand promotion and forms of sponsorship. Several web series are sponsored to depict the identity and value of the product in the storyline. One of the reasons brands create web series content is to help their audience connect directly with them. Through web series, the audience can also understand the value in the content. This research used mixed methods to find qualitative and quantitative data. The results show that most audiences are able to understand web series content as a form of brand value and identity. The four indicators measuring understanding of brand identity in web series show uniformity of positive values. The mean of the respondents' answers shows a number above 3 points. This indicates that the audience understands the existence of brand identity in web series content. Overall, respondents agreed that the web series was able to describe the four dimensions of brand identity. Four dimensions of brand identity that can be fully understood show that a web series can be a complete representation of a brand. This is in accordance with various previous studies, which explain that web series can be an alternative for introducing brand identity to specific segments